Apostolat biblijny świeckich: doświadczenia i nadzieje - Linke, Waldemar (Warszawskie Studia Teologiczne, 2018)
The paper is regarding the biblical apostolate of lay people: the history and first of all the doctrinal fundaments. The appreciation of this branch of this Church’s activity, the competences and duties of lay people is related to the task of clergy to assist the lay apostles and to help them to acquire the knowledge necessary for realize this service.